Penerapan Graphic Standard Manual pada Visual Identity Produk Komoditi Batik Berpotensi Ekspor - Sayekti, Pranti; Irawanto, Rudi (LPkM Universitas Bakrie, 2024)
Mahkota Laweyan is a Small and Medium Industry in the field of environmentally friendly batik and produces